Residualidade da forma e do modo de aplicação de calcário sobre atributos químicos do solo e de culturas - Spricigo, Jaqueline Gaio (2021)
A soil considered to be of good quality should allow for root growth without restrictions regarding chemical, physical and biological attributes and provide a greater volume of explored soil. The no-tillage system must have its attributes constantly monitored in order to predict future restrictions on root growth. In this sense, the objective of this work is to evaluate how the chemical attributes of the current soils are related to the liming and soil tillage carried out 25 years ago to correct the potential natural acidity in the transformation of the Pampa biome into a dryland forage and grain production area. The study was carried out in a plintic dystrophic Gray Argisol. The experimental design was randomized blocks and split plots, with four replications. The parcel constitutes the application modes of limestone, superficial and incorporated. The subplots consist of doses of limestone (0.0, 8.5 and 17.0 t ha-1 (half and total of the dose recommended by CQFS-RS/SC (1995)). In 2016, the limestone was re-applied superficially. The soybean root system was analyzed by means of root length, surface area, volume and mean diameter of the roots.For the chemical characterization of the soil, the active and potential acidity and the contents of available P and K and exchangeable Ca, Mg and Al were determined. were subjected to analysis of variance (in two-factor and three-factor arrangements) and, if there were significant differences, the means of treatments were compared by the Tukey test at 5% probability of error. the effects on the chemical attributes of the soil persist.The use of lime provided the neutralization of active acidity, potential acidity, increase in the contents of Ca2+ and Mg2- and decrease of Al3+. The reapplication of lime maintained the pronounced effects in the first layer (0- 7.5 cm). The dose was proportional to the amount of lime applied to neutralize the potential acidity. The soybean cultivar used is tolerant to conditions of aluminum saturation in the soil, not negatively affecting the components of the root system and showing no difference in productivity as a function of lime dose and application modes.